EFFECT OF PROFITABILITY, SOLVENCY RATIO, SIZE COMPANY, AND REPUTATION OF AUDITORS ON BOND RATING ON BANKING SECTOR. - Pinanditha, Adi Wira; Suryantini, Ni Putu Santi (E-Jurnal Manajemen, 2016)
This study aimed determine  the significance of the effect of of variable profitability, ratio of solvability, company size and reputation of the auditor’s against bond rating on the banking sector in Indonesia Stock Exchange 2012-2015 period. The population in this study is the banking sector in the Indonesia Stock Exchange 2012-2015 period totaling 54 companies. The sampling technique used was purposive sampling, in order to get many as 18 samples of the company’s banking sector. Data collection methods used in this study is a non-participant observational data obtained from www.idx.co.id . Technical analysis of the data used is the logistic regressions analysis with the help of SPSS 13 for windows. Result of the analysis showed that the particial profitability and solvency ratios significant negative effect on bond ratings, the size company’s significant positive effect on bond rating, and reputation auditor significant negative effect on thye bond rating.
Keywords: bond ratings, profitability, ratio of solvability, company size, reputation auditor